Modelling of household time constraints - Vuk, Goran (Proceedings from the Annual Transport Conference at Aalborg University, 2013)
The paper describes an activity based model for Copenhagen, introducing the concept of ‘Primary Family Priority Time’ (PFPT). We postulate that for pre-agreed workdays all family members spend time together at home in shared activities, e.g. dinner or childcare, and that PFPT has higher priority than each person’s own related activities, such as work and leisure. The conference paper presents the concept of PFPT and discusses how it fits into our demand model. Model estimation results are presented, including sub-models for PFPT participation, as well as its impacts in the model estimation results of the other model components.